A Case of Bilateral Multifocal Choroiditis Associated with BRAF/MEK Inhibitor Use for Metastatic Cutaneous Melanoma. (17th November 2022) - Yanagihara, Ryan T.; Tom, Elysse S.; Seitzman, Gerami D.; Saraf, Steven S.
ABSTRACT: Purpose: To report a case of BRAF/MEK inhibitor-associated multifocal choroiditis that recurred after medication re-exposure and resolved after discontinuing BRAF/MEK inhibition and administering local steroid therapy. Case Report: A 32-year-old woman with metastatic cutaneous melanoma on dabrafenib/trametinib presented with bilateral anterior uveitis and new bilateral multifocal chorioretinal scars. The anterior uveitis resolved after a course of topical steroids. She presented 18 months later with reactivation of bilateral multifocal choroiditis after starting encorafenib/binimetinib 1 month prior. The chorioretinal lesions appeared elevated with associated vitreous cell. Indocyanine angiography showed numerous foci of new choroiditis, more pronounced in the left eye. Encorafenib/binimetinib was discontinued and a subtenon triamcinolone injection was administered to the left eye. Her symptoms improved and the choroiditis resolved. Conclusion: BRAF/MEK inhibitors may be associated with ocular toxicity manifesting as multifocal choroiditis. The increasing use of these agents and risk of visual impairment warrants early detection and management.